2014
DOI: 10.1002/ijop.12077
|View full text |Cite
|
Sign up to set email alerts
|

Feelings and motives underlying Machiavellian behavioural strategies; narrative reports in a social dilemma situation

Abstract: This study explored the reasons and motives underlying the decisions of individuals with strong Machiavellian attitudes (High Machs). One hundred and fifty undergraduate students completed the Mach-IV test, and their contributions to, financial success in and narrative reports of a public goods game were analysed. High Machs contributed less to the public good and gained more benefit than Low Machs. Analysis of the narrative reports showed that High Machs used significantly fewer verbs referring to emotional i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 13 publications
(24 reference statements)
1
12
0
1
Order By: Relevance
“…Our finding, while exploratory, that Machiavellianism was a unique predictor of defection is consistent with past work which has found that Machiavellianism relates to exploitation in social dilemmas [ 20 , 23 , 24 , 25 , 26 , 45 ]. Our findings provide support for the notion that Machiavellian people are especially likely to successfully exploit others, and to gain from doing so [ 70 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our finding, while exploratory, that Machiavellianism was a unique predictor of defection is consistent with past work which has found that Machiavellianism relates to exploitation in social dilemmas [ 20 , 23 , 24 , 25 , 26 , 45 ]. Our findings provide support for the notion that Machiavellian people are especially likely to successfully exploit others, and to gain from doing so [ 70 ].…”
Section: Discussionsupporting
confidence: 92%
“…Bereczkei and Czibor [ 24 ] found that Machiavellianism was negatively correlated with contributions in a public good game and positively correlated with total profit gained by the end of the game. Other studies have found similar results, namely that individuals high in Machiavellianism contributed less to the public good and achieved relatively higher levels of personal gain in a public goods game [ 25 , 26 ]. These findings suggest that individuals high in Machiavellianism may be especially able to exploit others in contexts in which they stand to gain.…”
Section: Introductionmentioning
confidence: 52%
See 1 more Smart Citation
“…This leaves them free to analyze the situation dispassionately and proceed according to strategy. A recent analysis of narrative reports showed that high Machs use significantly fewer verbs when referring to emotional involvement, highlighting the importance of their cool and rational character (Czibor, Vincze, & Bereczkei, 2014).…”
Section: Emotional Coolnessmentioning
confidence: 99%
“…In the psychological literature, on the other hand, they have not been studied in conjunction, and there is a dearth of studies considering lay people representations on the common good and its financial provision. Although the financial contribution to the common good has been investigated in social dilemma research, the psychological literature has mostly focused on understanding why and when people make cooperative rather than selfish choices by examining a number of constructs ranging from internal psychological variables, such as social value orientation (Van Lange, 1999), Machiavellian traits (Czibor, Vincze, & Bereczkei, 2014), social identity (Brewer & Kramer, 807247S GOXXX10.1177/2158244018807247SAGE OpenCastiglioni et al research-article20182018 1 Università Cattolica del Sacro Cuore, Milan, Italy 1986), empathy (Batson et al, 1995), and emotions (Ketelaar & Tung Au, 2003), to external variables, such as incentives and sanctions (Molenmaker, De Kwaadsteniet, & Van Dijk, 2016), information (Van Dijk, De Kwaadsteniet, & De Cremer, 2009), and framing effects (Van Dijk & Wilke, 1997). However, all these studies tend to use money as a way to operationalize people's contribution rather than made it the object of study itself.…”
Section: Introductionmentioning
confidence: 99%